Kejadian Luar Biasa Malaria dengan Angka Kematian Tinggi di Kabupaten Dataran Tinggi Terpencil di Papua, Indonesia: Investigasi Epidemiologis - Robby Kayame; Emanuela Nirmala; Christine P.A. Korwa; Meidy Johana Imbiri; Hardiyanti Hardiyanti; Wahyuni Salewe; Anwar Mallongi (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
Malaria remains a major public health challenge in eastern Indonesia, particularly in the remote highland areas Papua, where access to health services is very limited. In early 2008, a suspected malaria outbreak with several deaths was reported in Agisiga District, a remote highland area in Papua. This study aimed to investigate the epidemiological characteristics, diagnostic results, and mortality patterns of the malaria outbreak as a basis for formulating future control strategies. The outbreak investigation was conducted using a cross-sectional design in Agisiga District from January to March 2008. Capillary blood samples were examined using Rapid Diagnostic Tests (RDTs) and thin blood smear microscopy. Malaria-related deaths were traced through verbal autopsy methods and interviews with families and community leaders. Descriptive analysis was performed to describe the demographic, clinical, and parasitological characteristics the cases. A total of 92 suspected malaria cases were identified, with the highest proportion coming from Tomosiga Village (52.2%), followed by Bigasiga Village (40.2%) and Agisiga Village (7.6%). Women accounted for 58.7% of all cases, and the most affected age group was 15–35 years (34.8%). Microscopic examination confirmed malaria infection in 55.0% of samples examined, with Plasmodium vivax predominating (45.0%), while the RDT positivity rate was much lower. The malaria outbreak in Agisiga District was characterized by high mortality, delayed diagnosis, and significant gaps in diagnostic capacity, particularly in remote villages. Strengthening the surveillance system, increasing diagnostic capacity, and improving access to timely treatment are crucial steps prevent similar outbreaks and reduce malaria mortality in the Papuan highlands.